Pengaruh Faktor Demografi dan Faktor Psikologi Investor dalam Pengambilan Keputusan Investasi di Era Ekonomi Digital - Asri Nur Wahyuni; Nugroho Heri Pramono (Universitas Pamulang, 2021)
AbstractAll forms of convenience in the digital economy era attract potential investors to invest, one of which is the existence of financial technology (fintech). On the other hand, technological advances have also made it easier for companies and governments to market their products and raise funds from the public. There are demographic and psychological factors in making investment decisions, especially in the digital economy era. Demographic factors reflect the characteristics of investors that are often a concern in influencing investment decisions. In addition, there are psychological factors that can also influence an investor when making investment decisions. The purpose of this study is to determine the influence of demographic factors and psychological factors of an investor in choosing investment instruments in the era of the digital economy. This study uses primary data by distributing questionnaires to respondents using google Forms. The analysis used in this study used descriptive analysis, frequency analysis, Crosstab - Chi-Square test, and hypothesis testing. Age and education as demographic factors have an influence on investment decisions. Demographic factors such as gender, marital status, and employment do not have an influence on investment decisions. Other results in this study indicate that psychological factors consisting of overconfidence, data mining, social interaction, emotion, and considering the past have an effect on investment decisions. Demographic factors with psychological factors in this study together have an influence on investment decisions. Keywords: demographic factors; psychological factors; investation decision AbstrakSegala bentuk kemudahan di era ekonomi digital menjadi daya tarik bagi para calon investor untuk berinvestasi salah satunya adalah keberadaan teknologi finansial (fintech). Di sisi lain, kemajuan tekhnologi juga memudahkan perusahaan dan pemerintah untuk memasarkan produknya dan pencarian dana dari masyarakat. Terdapat faktor demografi dan faktor psikologis dalam melakukan pengambilan keputusan investasi terutama di era ekonomi digital. Faktor demografi sebagai cerminan dari karakteristik investor yang sering menjadi perhatian dalam mempengaruhi keputusan investasi. Selain itu ada faktor psikologis yang juga dapat mempengaruhi seorang investor saat mengambil keputusan investasi. Tujuan penelitian ini untuk mengetahui pengaruh faktor demografi dan faktor psikologis seorang investor dalam memilih instrumen investasi di era ekonomi digital. Penelitian ini menggunakan data primer dengan menyebarkan kuesioner kepada responden menggunakan google form. Analisis yang digunakan dalam penelitian ini menggunakan analisis deskriptif, analisis frekuensi, Crosstab – Uji Chi Square dan uji hipotesis. Usia dan pendidikan sebagai faktor demografi memiliki pengaruh terhadap keputusan investasi. Faktor demografi berupa jenis kelamin, status pernikahan dan pekerjaan tidak memiliki pengaruh pada keputusan investasi. Hasil lainnya dalam penelitian ini menunjukkan bahwa faktor psikologi yang terdiri dari overconfidence, data mining, social interaction, emotion dan considering the past berpengaruh terhadap keputusan investasi. Faktor demografi dengan faktor psikologis dalam penelitian ini secara bersama – sama memiliki pengaruh terhadap keputusan investasi. Kata Kunci : faktor demografi; faktor psikologis; keputusan investasi